Extreme hourly 10m wind speed trends and reduced daily variability during 1940−2024 - Jia-Ning Song; Ming Sun; Zhi-Bo Li (Environmental Research Communications)
Near-surface wind speed (NSWS) is a critical atmospheric variable influencing Earth’s climate dynamics, weather patterns, ocean processes, ecological systems, and renewable energy resources. Utilizing the ERA5 global reanalysis dataset, this study systematically investigates long-term hourly NSWS trends from 1940 to 2024. Our findings highlight significant global increases in maximum, minimum, and daily mean hourly NSWS, with notably pronounced enhancements over oceanic regions. Crucially, minimum hourly NSWS has increased at a faster rate than maximum hourly NSWS, resulting in a widespread reduction of the daily NSWS range, particularly prominent across mid- and low-latitude oceans. This narrowing of wind speed variability potentially impacts marine ecosystems, coastal resilience, atmospheric boundary layer dynamics, and renewable energy production. The outcomes underscore the necessity and value of high-temporal-resolution analyses for capturing nuanced shifts in wind regimes, thereby providing essential insights into climate change’s complex, interrelated impacts on Earth’s environmental and socio-economic systems.